Antithrombotic therapy in antiphospholipid syndrome with arterial thrombosis: a systematic review and network meta-analysis - Attachaipanich, Tanawat; Aungsusiripong, Aimpat; Piriyakhuntorn, Pokpong; Hantrakool, Sasinee; Rattarittamrong, Ekarat; Rattanathammethee, Thanawat; Tantiworawit, Adisak; Norasetthada, Lalita; Chai-Adisaksopha, Chatree (Frontiers in Medicine, 2023)
Introduction The optimal secondary thromboprophylactic strategies for patients with antiphospholipid syndrome (APS) and arterial thrombosis remain controversial. This study aimed to evaluate the comparative efficacy and safety of various antithrombotic strategies in APS with arterial thrombosis. Methods A comprehensive literature search was conducted using OVID MEDLINE, EMBASE, Web of Science, and the Cochrane Controlled Register of Trials (CENTRAL) from inception until 30 September 2022, with no language restrictions. The inclusion criteria for eligible studies were as follows: inclusion of APS patients with arterial thrombosis, treatment with either antiplatelet agents, warfarin, direct oral anticoagulants (DOACs), or a combination of these therapies, and reporting of recurrent thrombotic events. Results We conducted a frequentist random-effects network meta-analysis (NMA) involving 13 studies with a total of 719 participants, comprising six randomized and seven non-randomized studies. In comparison to single antiplatelet therapy (SAPT), the combined use of antiplatelet and warfarin demonstrated a significant reduction in the risk of recurrent overall thrombosis, with a risk ratio (RR) of 0.41 (95% CI 0.20 to 0.85). Dual antiplatelet therapy (DAPT) showed a lower risk of recurrent arterial thrombosis compared to SAPT although the difference did not reach statistical significance, with an RR of 0.29 (95% CI 0.08 to 1.07). DOAC was associated with a significant increase in the risk of recurrent arterial thrombosis, with an RR of 4.06 (95% CI 1.33 to 12.40) when compared to SAPT. There was no significant difference in major bleeding among various antithrombotic strategies. Discussion Based on this NMA, the combination of warfarin and antiplatelet therapy appears to be an effective approach in preventing recurrent overall thrombosis in APS patients with a history of arterial thrombosis. While DAPT may also show promise in preventing recurrent arterial thrombosis, further studies are needed to confirm its efficacy. Conversely, the use of DOACs was found to significantly increase the risk of recurrent arterial thrombosis.